Strategi Meningkatkan dan Mengembangkan Kinerja Karyawan di Ossotel Legian - Galoja, I Made Opan Galoja; Kartimin, I Wayan; Putra, Putu Guntur Pramana (Universitas Triatma Mulya, 2022)
Ossotel Legian is a four-star hotel. Employees are a valuable asset owned by Ossotel Legian. The problems encountered are the lack of manpower when the room occupancy rate is above 60%, and the slow taking of work in completing the work that causes performance to decline. This problem will be discussed using the SWOT analysis technique. This research is qualitative research supported by the types and sources of data, namely qualitative and quantitative data as well as primary and secondary data. Data collection techniques used are observation, interviews, questionnaires, and documentation. The data analysis technique used is the SWOT analysis technique, namely analyzing internal factors (Strengths & Weaknesses) and external (Opportunities & Threats) with the help ofthe Internal-External Matrix and SWOT Matrix. The results of this study show that the strategies that can be applied at Ossotel Legian are SO Strategy: Strategy to Increase Employee Creativity, WO Strategy: Strategy to Increase Employee Motivation, ST Strategy: Strategy to Increase Cooperation among Employees, and WT Strategy: Employee Development and Training Strategy and Improvement Strategy Employee welfare.